2014
DOI: 10.1111/glob.12056
|View full text |Cite
|
Sign up to set email alerts
|

Between global dreams and national duties: the dilemma of conscription duty in the transnational lives of young Korean males

Abstract: In this study, I examine the dilemmas arising from the tension between citizen duties and youthful aspirations in a globalizing world. The state's requirement of military conscription structures the transnational lives of young Korean male migrants. More particularly, the timeline for serving the duty works as a primary temporal reference for the males' initial migration planning and future projections. Drawn from ethnographic fieldwork and in‐depth interviews among a community of young Koreans in New Jersey, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…But in a broader sense, we can expect the politics of citizenship and migration to make military service a contested issue in more and more countries with mandatory military service (according to World Population Review, this includes 68 countries today). States, on the one hand, show an increasing tolerance to dual and multiple citizenships (Harpaz 2019), while coincidingly preserving a conscription system that creates tension and requires constant dialogue with diaspora communities over civic duties and belonging (Song 2015; Thomson 1990). The interplay between the two conflicting ideas—acceptance of multiple citizenships (and symbolic belongings) and compulsory military service (in many cases a primary indicator of national loyalty)—asks for further research on how states regulate diaspora behavior on the one hand (Bauböck 2003), and how diaspora people navigate between conflicting obligations, expectations, and available life‐paths on the other.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But in a broader sense, we can expect the politics of citizenship and migration to make military service a contested issue in more and more countries with mandatory military service (according to World Population Review, this includes 68 countries today). States, on the one hand, show an increasing tolerance to dual and multiple citizenships (Harpaz 2019), while coincidingly preserving a conscription system that creates tension and requires constant dialogue with diaspora communities over civic duties and belonging (Song 2015; Thomson 1990). The interplay between the two conflicting ideas—acceptance of multiple citizenships (and symbolic belongings) and compulsory military service (in many cases a primary indicator of national loyalty)—asks for further research on how states regulate diaspora behavior on the one hand (Bauböck 2003), and how diaspora people navigate between conflicting obligations, expectations, and available life‐paths on the other.…”
Section: Discussionmentioning
confidence: 99%
“…While in both countries military service is viewed as a rite of passage, South Korea does not exclude emigrants and dual citizens from military duty. Studies showed that young Korean Americans engage in military service to secure both their legal and cultural citizenship and maximize future opportunities as cultural and business intermediaries (Choi and Chung 2018; Song 2015). It is impossible to know, however, how Korean emigrants would act in relation to military service had it been voluntary.…”
Section: Diaspora Military Service Homeland Programs and Return Migra...mentioning
confidence: 99%
See 1 more Smart Citation
“…In its governmental policies, public rhetoric, and educational programs, the Korean approach to international education has been more heavily centered on the neoliberal logic of global competitiveness. Since the 1990s, the Korean state has structurally and discursively promoted educational migration among young Koreans to advance the overall competitiveness of its citizens in the global economy (Song, 2015). Because the domestic economy depends heavily on export and foreign trade, employers generally prefer workers with US credentials, English proficiency, and global experience for managerial positions (Lee, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…In 2009, China made a major adjustment to the conscription policy and recruited young people with higher education enrollment, which provided a new direction to solve the problems of employment [2]. Different from other countries (such as South Korea), China adopted the conscription system that combines conscription with volunteer military service [3]. The implementation of the new military service law has included the college students who were originally listed as deferred enlistment in the range of enlistment, which makes more and more college students and graduates to enlist as a new choice for employment problem.…”
Section: Introductionmentioning
confidence: 99%